2022
DOI: 10.3390/cells11193137
|View full text |Cite
|
Sign up to set email alerts
|

The Toll-like Receptor 4 Polymorphism Asp299Gly Is Associated with an Increased Risk of Ovarian Cancer

Abstract: Ovarian cancer (OC) is one of the most common cancers threatening women’s lives around the world. Epithelial ovarian tumors represent the most common ovarian neoplasms. Most OC patients are diagnosed at the advanced stage, and there is an urgent need to identify novel biomarkers of the disease. Single-nucleotide polymorphisms (SNPs) in TLR genes may serve as crucial markers of cancer susceptibility. We investigated the frequency of TLR polymorphisms in a group of 200 women, including 70 with OC. Four SNPs, two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 80 publications
0
6
0
Order By: Relevance
“…They reported the highest frequency of heterozygous genotype and minor alleles of the polymorphism, which were AG and G, respectively. They concluded that the Asp299Gly variation could increase the risk of developing OC [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…They reported the highest frequency of heterozygous genotype and minor alleles of the polymorphism, which were AG and G, respectively. They concluded that the Asp299Gly variation could increase the risk of developing OC [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among the 70 women with ovarian cancer enrolled in the Poland study, the heterozygous variant and the recessive G allele of rs4986790 were more frequently found than in the 130 healthy individuals, indicating an increased risk of OC for its carriers. No difference in the distribution of rs4986791 between the cases and controls was observed [ 104 ]. A study conducted at the “Hippocratic” General Hospital of Athens, Greece, which included 261 breast cancer patients and 480 healthy individuals, showed that Gly carriers of rs4986790 (Asp/Gly & Gly/Gly genotype) and the Gly allele were more common among the breast cancer cases ( p = 0.0031 and p = 0.0061, respectively) [ 105 ].…”
Section: Discussionmentioning
confidence: 99%
“…In ovarian cancer, high expression of TLR4 and MyD88 was found to predict poorer overall survival in patients with EOCs [98]. A polymorphism in TLR4 was also found recently to be associated with increased ovarian cancer risk [99]. Of note, TLR pathways have dichotomous roles in cancer development [100].…”
Section: Common Innate Immune Program In Lpsmentioning
confidence: 96%